ORGANISATIONAL SUPPORT AND TEACHERS’ ENGAGEMENT FOR PROFESSIONAL DEVELOPMENT IN SECONDARY SCHOOLS OF NEPAL - Tamang, Sushma; Mishra, Anjay Kumar; Ghosh, Abhijit; Bhaumik, Amiya (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The teacher professional development program in Nepal is an ambitious initiative designed to support teachers’ professional growth. Organizational support and teacher engagement are of the utmost importance to ensure professional development. This study signifies the role of organizational support in enabling professional development and engaging teachers in teacher growth and development. This study aims to propose and rest an integrative model that views organizational supoort practices as a synergistic component that influences the sustainbility of teacher engagement. Survey-based cross-sectional data were collected from secondary schools in Kathmandu Valley using a structured questionnaire to teachers for this non-experimental correlational research design. Likert scales were used to express the perception-based data quantitatively and analyzed using regression models. This study confirms that organizational support procedures strongly influence professional development, highlighting organizational support as a moderator between teacher engagement and professional development. Organizational support also contributes to improving organizational performance. These practices are standard in Nepal schools but at a moderate level. However, schools are run for the benefit of one person only, so schools must be institutionalized with standard norms and values of participatory practices.